SUPERVISION OF THE PROSECUTOR IN UZBEKISTAN HISTORY OF DEVELOPMENT (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
this article describes in detail the content and development history of the prosecutor's control in Uzbekistan, the activities of the prosecutor's office in the years of the Second World War, the years after the war and the years of independence.